Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To convert the equation of a parabola from standard form to vertex form, we start with the given standard form of the parabola:
[tex]\[ x = y^2 + 10y + 22 \][/tex]
Our goal is to complete the square on the \( y \)-terms to rewrite this equation in vertex form. The vertex form of a parabola is given by:
[tex]\[ x = a(y - h)^2 + k \][/tex]
where \((h, k)\) is the vertex of the parabola.
Here are the steps to transform the equation:
1. Isolate the quadratic and linear terms involving \( y \):
[tex]\[ x = y^2 + 10y + 22 \][/tex]
2. Set up for completing the square:
To complete the square, we take the coefficient of the linear term (10), halve it, and square the result. This gives:
[tex]\[ \left( \frac{10}{2} \right)^2 = 25 \][/tex]
3. Add and subtract this square inside the equation:
[tex]\[ x = y^2 + 10y + 25 - 25 + 22 \][/tex]
4. Reorganize and simplify:
Group the perfect square trinomial and simplify the constants:
[tex]\[ x = (y^2 + 10y + 25) - 25 + 22 \][/tex]
[tex]\[ x = (y + 5)^2 - 3 \][/tex]
We have successfully rewritten the equation in vertex form. Therefore, the vertex form of the equation is:
[tex]\[ x = (y + 5)^2 - 3 \][/tex]
Now, let's match this to the given options:
A. \( x = (y + 10)^2 - 78 \)
B. \( x = (y + 5)^2 - 3 \)
C. \( x = (y + 5)^2 + 12 \)
D. \( x = (y + 10)^2 + 2 \)
The correct answer is:
[tex]\[ \boxed{B} \][/tex]
Thus, the vertex form of the equation is [tex]\( x = (y + 5)^2 - 3 \)[/tex].
[tex]\[ x = y^2 + 10y + 22 \][/tex]
Our goal is to complete the square on the \( y \)-terms to rewrite this equation in vertex form. The vertex form of a parabola is given by:
[tex]\[ x = a(y - h)^2 + k \][/tex]
where \((h, k)\) is the vertex of the parabola.
Here are the steps to transform the equation:
1. Isolate the quadratic and linear terms involving \( y \):
[tex]\[ x = y^2 + 10y + 22 \][/tex]
2. Set up for completing the square:
To complete the square, we take the coefficient of the linear term (10), halve it, and square the result. This gives:
[tex]\[ \left( \frac{10}{2} \right)^2 = 25 \][/tex]
3. Add and subtract this square inside the equation:
[tex]\[ x = y^2 + 10y + 25 - 25 + 22 \][/tex]
4. Reorganize and simplify:
Group the perfect square trinomial and simplify the constants:
[tex]\[ x = (y^2 + 10y + 25) - 25 + 22 \][/tex]
[tex]\[ x = (y + 5)^2 - 3 \][/tex]
We have successfully rewritten the equation in vertex form. Therefore, the vertex form of the equation is:
[tex]\[ x = (y + 5)^2 - 3 \][/tex]
Now, let's match this to the given options:
A. \( x = (y + 10)^2 - 78 \)
B. \( x = (y + 5)^2 - 3 \)
C. \( x = (y + 5)^2 + 12 \)
D. \( x = (y + 10)^2 + 2 \)
The correct answer is:
[tex]\[ \boxed{B} \][/tex]
Thus, the vertex form of the equation is [tex]\( x = (y + 5)^2 - 3 \)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.